2008
DOI: 10.5664/jcsm.27347
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Therapy of Obstructive Sleep Apnea in Type 2 Diabetics Improves Glycemic Control During Sleep

Abstract: SciEnTific invESTigATiOnSBackground: Type 2 diabetes and obstructive sleep apnea (OSA) are frequently comorbid conditions. OSA is associated with increased insulin resistance, but studies of continuous positive airway pressure (CPAP) have shown inconsistent effects on glycemic control. However, endpoints such as hemoglobin A1c and insulin sensitivity might not reflect short-term changes in glycemic control during sleep. Methods: We used a continuous glucose-monitoring system to measure interstitial glucose eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 27 publications
2
57
0
2
Order By: Relevance
“…However, the level of control is far from optimal level as found in a recent study 49 . While some studies found that treatment of OSA improves A1C, the results are inconsistent 7,29,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the level of control is far from optimal level as found in a recent study 49 . While some studies found that treatment of OSA improves A1C, the results are inconsistent 7,29,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OSA is commonly associated with known diabetic complications 4,[9][10][11]25,26 . Lastly, screening and initiation of treatment may contribute to prevention and improved control of co-morbid conditions 16,[27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been proposed that the recovery of breathing disturbances during sleep can improve several markers of DGM and insulin resistance, such as glycated haemoglobin, fasting glucose and insulin (29). Sleeping and nocturnal hyperglycaemia were reduced during CPAP treatment in the group of mostly obese type 2 DM with moderate to severe, mostly severe OSAS (30). Another study determined that CPAP therapy improved both excessive daytime sleepiness and insulin resistance in patients with OSAS having excessive daytime sleepiness (7).…”
Section: Discussionmentioning
confidence: 99%
“…2 The results of experimental studies evaluating effects of OSA treatment in hypertension reveal modest benefi ts, 3,4 and the data regarding improvement in glucose homeostasis in type 2 diabetics from small clinical trials are inconsistent. 5,6 This discrepancy is partly due to the size and type of cohorts examined or the specifi c outcomes assessed. 7 Several studies examined populations with differential baseline characteristics (presence or absence of preexisting hypertension/diabetes) or variable OSA disease severity.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%